TERMS, SEMITERMS AND PSEUDOTERMS IN TECHNOEDUCATION AND INFOEDUCATION - STOFFA, Jan; STOFFOVA, Veronika (Trends in education, 2015)
The study clarifies the concepts semiterm and pseudoterm in relation to the concept (notions) term, and responds to frequent improper using of semiterms and pseudoterms in educational practice. From pseudoterms it pays special attention to the use of names, especially trade names, colloquial words and substandard verbal expressions, especially slang and professionalisms, instead of right literary terms. It calls on the responsible and critical approach of educators and authors of written educational information sources to those categories of improper compensation terms. It also gives a range of improper use semiterms and pseudoterms in terminological and educational practice in the field of techoeducation and infoeducation.
Keywords: term; semiterm; pseudoterm; improper substitutions of terms; technoeducation; infoeducation.